Diospyros barteri Hiern (Ebenaceae): new records for the vascular flora of Benin - Dassou, G.H.; Adomou, A.C.; Kpetikou, C.G.; Neuenschwander, P. (Pensoft Publishers, 2024)
Diospyros barteri was recorded for the first time from Dodja, a sacred forest in the Commune of Abomey-Calavi, Benin. We provide a detailed description, illustration, habitat, ecology, flowering period, and population size of this species. These occurrences fill a gap in the distribution of the species in the Dahomey-Gap territory. Our new records show the importance of botanical surveys in sacred forests which are hotspots of biodiversity in the country. However, sacred forests are unfortunately poorly maintained and managed and are difficult to access because they serve as central sites for ceremonies of local divinities in vodun celebrations.